Pelatihan Dokter Kecil Sebagai Upaya Penguatan Program Usaha Kesehatan Sekolah Di SDN 05 Surau Gadang Pasca-Pandemi Covid-19 - Ida Rahmah Burhan; Husna Yetti; Ken Rabbani Faathira; Dwi Putri Herinda; Dara Indah Genia; Hafiznie Ansharina; Muhammad Zhorif Sulthani (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Elementary schools are strategic environments for developing healthy lifestyles from an early age through a promotive and preventive approach. The little doctor training program as school health cadres is one effective strategy for strengthening School Health Program (UKS). The training was initiated as a post-COVID-19 pandemic recovery program to revitalize UKS in response to the low implementation of UKS and the high percentage of students who have not implemented Clean and Healthy Living Behaviours (PHBS). To increase the capacity of students at SDN 05 Surau Gadang as school health cadres to achieve school health empowerment. The training was conducted in collaboration with the Nanggalo Community Health Centre with group-based interventions for 63 students in grades 3–5 at SDN 05 Surau Gadang, which included the delivery of material on UKS, PHBS, Primary Preventive Care (P3P), and First Aid for Accidents (P3K), as well as hands-on practice in six-step hand washing and first aid simulations. Evaluation was conducted using pre-tests and post-tests. There was an increase in the average knowledge score from 65.56 to 71.59 (p = 0.019), and the proportion of students in the “good” category increased from 36.5% to 46%. Little doctor training is effective in improving understanding of PHBS and UKS and forming independent elementary school health cadres. This program positively impacts the capacity of community health centres in optimizing ongoing little doctor training programs post-pandemic.